Pengaruh Penggunaan E-Modul Berbasis Project Based Learning Terhadap Hasil Belajar Kontruksi Jalan dan Jembatan Siswa Kelas XI di SMKN 1 Sumatera Barat - Christina Mentari Perdana; Nadra Mutiara Sari; Rijal Abdullah (Teknik Sipil Universitas Negeri Padang, 2020)
This study aims to show how the effect of using e-module based on Project-based Learning on learning outcomes in the Road and Bridge Construction subject for class XI students of SMKN 1 West Sumatra. This type of research is quasi experimental and the research design used is nonequivalent.control.group.design. The samples used in this study were 33 students consisting of 15 students in Class A as the experimental class and 18 students in Class B as the control class. The results of the data obtained from this study were obtained from the pretest results before being given teaching and the post-test results after being taught. The results that have been obtained are then analyzed using the t-test to determine the hypothesis of the study. Based on the hypothesis testing, it was found that tcount 2.204> ttable 5% = 2.0231 then it can be analyzed that there is a relevant influence on improving student learning outcomes in learning by using e-module. Roads and Bridges in class XI DPIB SMKN 1 West Sumatra.